A study of students conceptual understanding of Newtonian mechanics in Afghanistan / Abdul Manan Hairan - Hairan, Abdul Manan (2019)
This research was conducted to investigate the level of conceptual understanding of Newtonian mechanics among Afghan school and university students in Kabul, Afghanistan. This study employed a quantitative descriptive survey method where the Pashto version of the Force Concept Inventory (FCI) was given to a random sample of 216 school and 90 university students. The collected data was analysed using SPSS v.24 where descriptive and inferential statistical analysis methods were used to determine the level of students' conceptual understanding of Newtonian mechanics. The findings show that the average FCI scores obtained by the school and university students were 20% and 26% respectively. The results of the study reveal that generally, Afghan students had low level of Newtonian mechanics conceptual understanding which is less than the entry threshold for FCI. Furthermore, the results of inferential statistics indicate that student's first language, gender, school, or university didn't have any significant effect on the test scores of school and university students. In the meantime, students from both levels, school and university, had various misconceptions regarding each concept in the six conceptual dimensions of the FCI test. In general, the results confirmed that both school and university students are having difficulties to conceptually understand Newtonian concepts. The average FCI score of Afghan school and university students is lower than the average scores of students from other countries such as USA, UK, China, Russia, Japan, Finland, Africa, Turkey, Saudi Arabia, Thailand, India, Indonesia and Malaysia. However, the Afghan school students result is slightly better than that of Philippines and Iran, while the university students result is better than Laos. Finally, recommendations are made for conceptual learning, effective teaching method as well as for further research.